Digital control of a voltage-mode synchronous buck converter - Oliva, Alejandro Raul (2006)
A digital control algorithm capable of separately specifying the desired output voltage and transient response for a synchronous buck converter operating in voltage mode was developed. This algorithm is based on superimposing a small control signal onto a voltage reference at each switching cycle to cancel out the perturbations. A zero steady-state error in the output voltage can be obtained with the aid of additional dynamics to allow the controller to track a load change and update the reference to a new load state. The specifications of the control algorithm are achieved by pole placement using complete state feedback. The control algorithm was implemented on a digital signal processor (DSP)-controlled synchronous buck converter.